In the belly of the beast: resolving stomach tag data to link temperature, acceleration and feeding in white sharks (Carcharodon carcharias). Issue 1 (December 2015) - Jorgensen, Salvador; Gleiss, Adrian; Kanive, Paul; Chapple, Taylor; Anderson, Scot; Ezcurra, Juan; Brandt, W.; Block, Barbara
Abstract Background Motion detecting archival data loggers such as accelerometers have become increasingly important in animal biotelemetry and offer unique insights into animal behavior, energetics, and kinematics. However, challenges remain for successful deployment and interpretation of data from captive and wild animals. Accelerometer sensors require being packaged in an archival tag that has a firm attachment in a fixed (known) orientation to accurately measure the relevant motion of the animal. This requirement can lead to handling stress and attachment techniques that can affect the tagged animal's natural behavior and welfare, and lead to behavioral artifacts in the data. Accelerometer data also require careful interpretation to correctly identify behavioral events of interest such as foraging. For endothermic species, changes in stomach temperature can produce temperature signatures indicative of foraging events. In this paper, we present a novel method for recording foraging events in free-swimming white sharks. Methods We used a combination of accelerometer loggers and pop-up archival transmitting (PAT) tags (MK10, Wildlife Computers) to examine the feeding and kinematics of white sharks (Carcharodon carcharias ) in the wild. We validated feeding results using a captive juvenile white shark where controlled feeding experiments could be conducted in an aquarium setting at the Monterey Bay Aquarium. We fed data logger instrument packages to eight free-swimming white sharks. Deployment durations ended naturally when the package was regurgitated and ranged from 2 to 12 days. While inside the stomach, the orientation of the data logger package was arbitrary and resulted in slow shifting over time, a challenge for normal analysis routines. We present one of these datasets to illustrate a novel methodology for calibrating accelerometer orientation, and evaluate the utility of resulting data. Results We obtained accurate accelerometer measurements including surge, heave, and sway from data loggers with shifting orientation through data post-processing. We measured consistent dips in stomach temperature followed by a steady prolonged heating during controlled feeding events in a captive white shark. Similar thermal signatures identified in wild white shark records confirmed feeding events while acceleration data characterized the associated prey capture behavior. Conclusions We provided proof of concept for a novel and non-invasive technique for accelerometer data logger deployment extending the possibilities for their use in bio-logging. The placement of data-logging tags in the stomachs of endothermic white sharks produced high quality tri-axial acceleration data in addition to stomach temperature data capable of detecting feeding events. The technique has the potential for distinguishing between attempted and successful foraging events. This approach to accelerometer coordinate correction could be applied in other systems where logger orientation is unknown or changes after deployment.